M13 Outpatient ultrasound-guided fine-needle aspiration of supraclavicular lymph nodes, performed by chest physicians for diagnosis and staging of lung cancer. (14th November 2013) - Ahmed, R; Slade, MG
Abstract : Introduction and Objectives: Supraclavicular fossa (SCF) lymph node metastases are detectable in almost half of lung cancer patients where mediastinal lymphadenopathy is present (1). They represent N3 disease, not amenable to radical treatment. Ultrasound guided fine needle aspiration cytology (US-FNAC) is a sensitive test in this setting. We explored the accuracy of outpatient US-FNAC of SCF nodes performed by respiratory physicians. Methods: Outpatients with suspected lung cancer were selected for US guided FNAC of SCF lymph nodes if they had one or more of: 1. Enlarged SCF lymph nodes on CT scanning 2. Palpable supraclavicular lymph nodes 3. Visible non-enlarged SCF lymph nodes on CT with associated mediastinal lymphadenopathy. After informed consent, the SCF was scanned with the patient semi-recumbent, using a Sonosite US with 13.6MHz linear probe, by MGS, or RA supervised by MGS, a level-2 non-radiologist US practitioner. Real-time US-FNAC was performed using a 21G or 19G needle and the capillary aspiration technique. Three passes were made and cores were put into a cytology fixative (Cytolyt). Results: 14 patients (male = 8, median age 67.5 years) underwent US-FNAC. The median short-axis diameter of the target node was 11.5 mm (range 5–25 mm). A positive malignant diagnosis was obtained in 11/14 patients (78.6%), (adenocarcinoma n = 6, small cell lung cancer n = 4, non-small cell lung cancer n = 1), and all four sub-centimetre nodes gave positive results. There were two false-negatives (14.3%) on an intention-to-diagnose basis, in one of whom no specimen could be obtained. One sample was non-diagnostic. All patients found the procedure easy to tolerate and there were no complications. Discussion: US-FNAC is well tolerated and can be safely performed opportunistically by respiratory physicians during outpatient visits. The diagnostic yield is high and comparable with previous published series. Its incorporation into the lung cancer pathway can facilitate prompt diagnosis and staging without more invasive investigations. Reference: Fultz PJ, Feins RH, Strang JG et al. Detection and diagnosis of nonpalpable supraclavicular lymph nodes in lung cancer at CT and US. Radiology 2002;222 :245–51.